Penguatan Usahatani dan Tata Kelola Kelembagaan Organisasi Petani Tembakau Desa Japeledok, Kecamatan Pancur, Kabupaten Rembang - Putro, Tetuko Rawidyo; Sistriatmaja, Muhammad Bagus; Hakim, Lukman; Mulyanto; Rahayu, Siti Aisyah Tri; Sumantyo, Riwi; Jati, Hery Sulistyo; Johadi; Nugroho, Ariyanto Adhi; Purnama, Muhammad Yusuf Indra (Yayasan Sagita Akademia Maju, 2024)
The Japeledok Village Tobacco Farmers Group was recently established with a simple organizational structure due to a lack of insight into institutional organization. This becomes an obstacle in the continuity of the organization in the Farmer Group. One of the programs that is a priority for the Farmer Group is the use of Farmer Group land by cultivating tobacco in order to increase income. The obstacle faced by most Farmer Group members is that the tobacco they cultivate cannot grow optimally. The solution offered is to improve the skills of Farmer Group members in crop production on land and provide assistance regarding the institutional design of an organization to strengthen the knowledge and insight of Farmer Group members in running the organization. The implementation method is through training, mentoring and practice for Farmer Group members. Training and assistance in tobacco production. Training and assistance in managing organizations as well as understanding the basics of organizational institutional design. The results obtained from training on tobacco cultivation techniques for Farmer Group members are an increase in the knowledge and skills of Farmer Group members in tobacco plant production. Most of the harvest is sold within the Farmer Group members, so that the turnaround of small-scale businesses has been successfully implemented. The result of training and assistance in organizational governance is that the administrators and members of the Farmer Group are able to prepare basic budgets/household budgets. Increasing the active role of Farmer Group members in organizations is important for the sustainability of the existence of an organization.